2015
DOI: 10.1155/2015/952536
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging and Diverse Roles of Src‐Like Adaptor Proteins in Health and Disease

Abstract: Although Src-like adaptor proteins (SLAP-1 and SLAP-2) were mainly studied in lymphocytes, where they act as negative regulators and provide fine control of receptor signaling, recently, several other functions of these proteins were discovered. In addition to the well-characterized immunoregulatory functions, SLAP proteins appear to have an essential role in the pathogenesis of type I hypersensitivity, osteoporosis, and numerous malignant diseases. Both adaptor proteins are expressed in a wide variety of tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…Of the 22 positional candidate genes identified in the 47 identified QTL, 10 were identified as potential functional candidate genes based upon their gene ontology results and previous reports on their function in the literature (Bannantine and Bermudez, 2013;Liu et al, 2013;Marton et al, 2015). Some of these genes are novel in the sense that they have not previously been associated with bovine paratuberculosis.…”
Section: Candidate Genes Associated With Humoral Response To Mapmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 22 positional candidate genes identified in the 47 identified QTL, 10 were identified as potential functional candidate genes based upon their gene ontology results and previous reports on their function in the literature (Bannantine and Bermudez, 2013;Liu et al, 2013;Marton et al, 2015). Some of these genes are novel in the sense that they have not previously been associated with bovine paratuberculosis.…”
Section: Candidate Genes Associated With Humoral Response To Mapmentioning
confidence: 99%
“…The src-like adaptor protein 2 (SLAP-2), encoded by SLA2, has been observed to be expressed in the small intestine, colon, spleen, and lymph nodes in humans (Fagerberg et al, 2014). As reviewed by Marton et al (2015), SLAP-2 negatively regulates the antigen receptor signaling action of both B and T lymphocytes, thus suppressing host immune responses. It has also been suggested that SLAP-2 is necessary for the maturation and activation of mono-Journal of Dairy Science Vol.…”
Section: Zbtb20mentioning
confidence: 99%
“…A previous study demonstrated that the migration activity of murine fibroblast cells in Src-knockout rats is reduced, which further supports the role of Src in cell migration (22). The interactions between Src, the extracellular matrix and integrin are essential for the induction of ras homolog gene family, member A (RhoA), and in turn, the activation of RhoA is closely associated with cell migration (23). The present study revealed that mechanical stress significantly suppressed Src protein expression in OLF cells.…”
Section: Discussionmentioning
confidence: 58%
“…SLA 2 is known to be involved with signal transduction in B and T cells. Further, SLA 2 downregulates humoral and cell-mediated immune responses, by contributing to a correct lymphocytes’ activation and proliferation [73,123,124]. SLA 2 antagonistic effect on lymphocytes proliferation would suggest its putative involvement in opposing the diffusion of T. parva parva in the organism.…”
Section: Discussionmentioning
confidence: 99%